The Role of Nitric Oxide in the Antidepressant Actions of 5-Aminoimidazole-4-Carboxamide-1-β-D-Ribofuranoside in Insulin-Resistant Mice. Issue 1 (January 2016) - Liu, Weina; Wang, Yangkai; Li, Haipeng; Ji, Liu
ABSTRACT: Objective: Depression and Type 2 diabetes mellitus are interrelated conditions, but the underlying neurobiology is insufficiently understood. The current study compared the effects of a pharmacological manipulation with 5-aminoimidazole-4-carboxamide-1-β-D-ribofuranoside (AICAR) that targets neurobiological processes by adenosine 5′-monophosphate–activated protein kinase activation versus exercise on depression-like behavior and nitric oxide (NO)–related measures. Methods: A mouse model of a depression-like and insulin-resistant state, induced by the co-treatment of high-fat diet and corticosterone administration, was used to examine the antidepressant action of AICAR and exercise. Results: Data showed that AICAR was a putative antidepressant in the depression-like and insulin-resistant mice (total ambulatory distance in the open-field test was 5120.69 ± 167.47 cm, mobility duration in the forced swim test was 17.61 ± 1.54 seconds, latency to feed in the novelty suppressed feeding test was 255.67 ± 37.80 seconds; all p values < .05). Furthermore, the antidepressant actions of AICAR required endothelial nitric oxide synthase activity with increased NO production in the prefrontal cortex, whereas corticosterone-induced expression of neuronal nitric oxide synthase and NO production may increase the risk of depression. In contrast to the traditional antidepressants such as ketamine and imipramine, AICAR interfered with the effects of insulin in skeletal muscle in the context of high-fat diet, consistent with the potential antidepressant effects of AICAR. Exercise also resulted in activation of adenosine 5′-monophosphate–activated protein kinase, nitric oxide synthase, and NO production (all p values < .01), which in turn may be implicated in the antidepressant effects of exercise. Conclusions: These findings suggest that NO is an essential signal mediating the antidepressant actions of AICAR. Ultimately, the concurrent effects of AICAR on brain insulin action and mitochondrial function suggest a potential of neural insulin resistance, which may contribute to our understanding of the comorbidity of depression and Type 2 diabetes. Abstract : Supplemental digital content is available in the text.